Studi Komparatif Metode Qiyasiyah dan Istiqroiyah dalam Pembelajaran Nahwu di Pondok Pesantren - Khabibul Khoiri (Departement of Mathematics Education, 2024)
This research is motivated by the significant differences in the use of nahwu learning methods in Salaf and modern Islamic boarding schools. This phenomenon is influenced by the existence of different learning objectives, therefore there are two main methods in learning nahwu, namely the qiyasiyah and istiqraiyah methods which are then compared to find out where the similarities and differences between the two are. The research results from this research are the similarities between the qiyasiyah and istiqraiyah methods, namely first, that in the learning process the material of the rules is presented along with examples, the two rules are studied in stages. The differences between the two are first, in terms of application, the majority of the qiyasiyah method is applied in Salaf Islamic boarding schools, while the istiqroiyah method is applied in modern Islamic boarding schools, secondly, in terms of learning steps, the qiyasiyah method begins with an explanation of the rules and continues with examples in Arabic sentences, while the istiqraiyah method begins with an example and continues with an explanation of the rules, third, in terms of breadth of material, the qiyasiyah method provides a broad explanation of the rules up to the discussion of furu' while the istiqraiyah method is more about explaining basic rules, fourth, in terms of the effectiveness of application in language Active Arabic, the Qiyasiyah method is less effective. When applied to active Arabic, considering that the environment in Salaf Islamic boarding schools focuses more on qira'ah skills, while the Istiqroiyah method is more effectively applied in modern Islamic boarding schools because it emphasizes Kalam skills, the five Qiyasiyah methods emphasize memorizing rules. rather than practicing making examples of Arabic sentences, while istiqroiyah places more emphasis on the practice of making examples rather than memorizing rules.